PHƯƠNG PHÁP ƯỚC TÍNH ĐỘ CHÍNH XÁC VỊ TRÍ MẶT BẰNG ĐIỂM LƯỚI GPS - Hiến, Phan Văn (Vietnam Journal of Earth Sciences, 2017)
In the paper, the author proposed the method for rigorous accuracy estimation of horizontal points of GPS network. In order to prove the correctness of the method, the author compared the results of accuracy estimation according to this method with the results of accuracy assessment after adjusting 5 GPS networks, which are set upand adjusted by GPSurvey software.